(untitled) (REMUNOM, 2025)
Cardiovascular diseases remain the leading cause of mortality worldwide, demanding increasingly accurate diagnostic strategies. In this context, enzymatic biomarkers have become essential tools in clinical practice, enabling the identification of myocardial injury, risk stratification, and therapeutic monitoring. This article discusses the historical evolution of biomarkers, from classical enzymes such as CK-MB and LDH to modern markers like high-sensitivity troponins and natriuretic peptides (BNP and NT-proBNP). Their clinical applications, technological advances, limitations, and future perspectives are analyzed, emphasizing the role of biomarkers in personalized and preventive medicine.